WUT's the deal? a study on the relationship between the WUT criteria and urine-specific gravity as markers of hydration status in collegiate long-distance runners and walkers - Dungca, Ivan Gregory R. 1999-
Hydration is an important, but underemphasized, aspect of athletic performance. Studies have shown that dehydration may lead to detriments in both performance and health. A diagnostic tool for hydration status (WUT criteria) has been introduced, however, only one study has tested its validity in assessing hydration status against urinary markers. Therefore, the study seeks to further examine the relationship between the WUT criteria and urine-specific gravity (USG) in assessing hydration status among collegiate long-distance runners and walkers. Samples were taken from five collegiate long-distance athletes (21.8 ± 2.17 years) who participated in a 7-day protocol. Measurements of USG, urine color, body mass, and thirst sensation were recorded. No significant correlation was found between USG and the WUT criteria (r = .310; p = 0.183) and no significant differences in USG were found between the WUT criteria markers (p = 0.959; p = 0.154;p = 0.144). Since no significant relationship between USG and the WUT criteria was found for this sample, the researcher cannot recommend using the WUT criteria as a diagnostic tool for long distance runners and walkers. Further research is needed to better understand the relationship between the WUT criteria and USG as markers of hydration status in the population